2022
DOI: 10.33642/ijbass.v8n3p3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Economic Mobility on Decision-Making and Behavior: A Succinct Review and Future Research Directions

Abstract: Research in marketing and psychology has shown that individual perception of economic mobility varies widely even in a single society and systematically influences decision-making and behavior across different domains. The objective of this paper is to introduce this important construct to researchers in other fields so that they can utilize and further develop it in future research. In particular, this paper highlights differences between perceived economic mobility and observed economic mobility and provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Second, given that modern society is built on the premise that everyone has opportunities to pursue upward economic mobility, and given that hard work, rather than circumstances at birth, is the main driver of economic success (Morgan, 2006), we highlight the role of perceived economic mobility as a core principle of modern society that also shapes pro-environmental behavior. This is a novel contribution since the growing literature on perceived economic mobility has, so far, documented its effects predominantly in consumption settings (Kim, 2022). Third, we add to the literature by showing the important role played by future orientation in determining proenvironmental behavior.…”
Section: Introductionmentioning
confidence: 75%
“…Second, given that modern society is built on the premise that everyone has opportunities to pursue upward economic mobility, and given that hard work, rather than circumstances at birth, is the main driver of economic success (Morgan, 2006), we highlight the role of perceived economic mobility as a core principle of modern society that also shapes pro-environmental behavior. This is a novel contribution since the growing literature on perceived economic mobility has, so far, documented its effects predominantly in consumption settings (Kim, 2022). Third, we add to the literature by showing the important role played by future orientation in determining proenvironmental behavior.…”
Section: Introductionmentioning
confidence: 75%
“…Out of eight participants, only two indicated that emotions have most influenced their decision-making process, the remaining six stated that only in few occasions or sometimes the emotions have influenced their decision-making. One of the participants stated, “I am very rational at decision-making and do not allow emotions to interfere on my decisions.” In this respect, Kim (2012) explained that “emotions interfere on rationality, affecting one’s objective observation of the situation, as there is a complementary relationship between both, as an emotion has an important role in the decision-making process.”…”
Section: Discussionmentioning
confidence: 99%
“…One of the participants stated, "I am very rational at decision-making and do not allow emotions to interfere on my decisions." In this respect, Kim (2012) explained that "emotions interfere on rationality, affecting one's objective observation of the situation, as there is a complementary relationship between both, as an emotion has an important role in the decision-making process. "…”
Section: Discussionmentioning
confidence: 99%